Predictors of treatment outcomes in multi-drug-resistant tuberculosis in India (2015–2025): A systematic review. - Panda, Suvendu Kumar; Mishra, Pratyush; B. Jagadish; Panigrahy, Srikanta; Panda, Manisha (Student's Journal of Health Research Africa, 2025)
Background: Multi-drug-resistant tuberculosis (MDR-TB) remains a major public health concern in India, with treatment outcomes often falling below global targets. Identifying predictors of treatment success or failure is critical for improving care and informing national strategies. Objectives: To systematically review and synthesize the evidence on predictors of treatment outcomes in MDR-TB patients in India between 2015 and 2025. Materials and Methods: Electronic databases (PubMed, Scopus, Google Scholar) were searched from January 2015 to May 2025. Additional articles were identified through manual reference screening. The review included observational studies on Indian patients receiving MDR-TB treatment under programmatic or hospital-based settings. Risk of bias was assessed using the Newcastle-Ottawa Scale. Data were categorized thematically into demographic, clinical, comorbidity, and treatment-related predictors. Results: Seven studies were included, with sample sizes ranging from 95 to over 2,000 patients. Common predictors of unfavorable outcomes included older age, male sex, undernutrition (low BMI/albumin), HIV co-infection, substance use (alcohol/smoking), poor adherence, and adverse drug reactions. Treatment success rates were generally below 50%. Conclusions and Implications: Multiple modifiable and non-modifiable factors contribute to poor MDR-TB outcomes in India. Addressing undernutrition, supporting adherence, and managing comorbidities like HIV and substance abuse can improve outcomes. These findings can inform targeted interventions under the National TB Elimination Programme.